Chapter Wealth inequalities in cities of the Polish-Lithuanian Commonwealth and their changes during the seventeenth century. Sources and methods of measure - Wagner, Katarzyna (Datini Studies in Economic History, 2020)
I would like to determine the evolution of wealth concentration in main cities of the Polish-Lithuanian Commonwealth by comparing the data from different benchmark years. Moreover, I will analyze whether the Gini coefficient value indeed refers to the communities who are at a threshold of economic growth, and what is the correlation between the value of the coefficient and the town or city's economic situation. Also, it is worthwhile to ponder the question: is there any correlation - noted by both Jan Luiten van Zanden and Guido Alfani - whereby the larger the town/city, the more visible the inequalities. Finally, how do the towns/cities of the Polish-Lithuanian Commonwealth compare to those in Western Europe.